SHARIA BANKING AS A MEANS OF PROSECUTION AND STRENGTHENING THE COMMUNITY'S ECONOMY - Himmatul Udzma; Ach Jalaluddin Ar-Rumi (IZZI: Jurnal Ekonomi Islam, 2025)
Islam is not only limited to matters of worship and faith, more than that, Islam also plays a role,in providing solutions,to.real problems,faced.by society, one of which,is.the problem of_the community's,economy..This article discusses the,role.of Islamic banking as a means of da'wah in strengthening the community's,economy. The purpose,of/this writing is-to provide a strong understanding to the community that da'wah is,not-only in the-form of,lectures and religious studies but also strengthening the community's, economy.is part-of da'wah, especially Islamic banking products that are based on muamalah laws. So that the relationship or function of da'wah in Islamic banking can be found which in the end with the islamic banking da'wah approach can be accepted by the community and avoid values that conflict with religion. This study uses qualitative descriptive research with a literature review approach, using primary and secondary data related to the title of the study above, so it can be concluded that in carrying out its transactions, Islamic banking does not only look at the benefits or banking benefits alone but also provides an understanding of the correct muamalah but also provides a real impact on the community whose customers become banks, namely stopping the practice of usury, and other transactions that are mixed with the Islamic religion, so this study will be a benchmark for how important Islamic banking is as a means of preaching to the community so that they transact in everyday life while still being based on religious values and this is the essence of preaching in Islam.